The Rabbi and the Mancebo: Arévalo and the Location of Affinities in the Fifteenth Century. - Gutwirth, Eleazar (Medieval Encounters, 2018)
The background to this paper is the difference between occasionally atemporal and multinational approaches and local, historical approaches to religious ideas and encounters. The chosen example is that of two authors from one town (Arévalo) and one historical moment (fifteenth-century Castile). The article attempts firstly to identify stylistic, rhetorical, and literary elements in the historiographic traditions about the reputation of the town. Secondly it points to the changes in the status of the town in the late Middle Ages that affected Christians, Muslims, and Jews. Thirdly, after identifying certain tendencies in the writings of the two authors from the town, one Muslim (known as the Mancebo de Arévalo) and the other Jewish, Rabbi Yosef ibn Ṣaddiq de Arévalo, it searches for affinities and common elements in their attitudes.